Measurement of inclusive jet cross sections in Z/γ*(→e+e-) +jets production in pp̄ collisions at s=1.96 TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
Inclusive jet cross sections in Z/γ* events, with Z/γ* decaying into an electron-positron pair, are measured as a function of jet transverse momentum and jet multiplicity in pp̄ collisions at s=1.96 TeV with the upgraded Collider Detector at Fermilab in run II, based on an integrated luminosity of 1.7 fb-1. The measurements cover the rapidity region |yjet|<2.1 and the transverse momentum range pTjet>30GeV/c. Next-to-leading order perturbative QCD predictions are in good agreement with the measured cross sections. © 2008 The American Physical Society.